Traditional way of learning Ayurveda and practising it : a dialogue with Vaidya Bhaskarbhai Hardikar - Dixit, Mukund R., (SAGE Knowledge. Cases., 2014)
Vaidya Bharskarbhai Hardikar is an Ayurveda practitioner trained through the traditional system of education. This interview with Hardikar reveals his personal process of learning Ayurveda, and how he applies it in practice. This case provides an excellent demonstration of different methods of knowledge acquisition and management, as Hardikar learned his skills through a variety of diverse methods.